2021
DOI: 10.1111/nan.12765
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐142‐3p regulates synaptopathy‐driven disease progression in multiple sclerosis

Abstract: Aim We recently proposed miR‐142‐3p as a molecular player in inflammatory synaptopathy, a new pathogenic hallmark of multiple sclerosis (MS) and of its mouse model experimental autoimmune encephalomyelitis (EAE), that leads to neuronal loss independently of demyelination. MiR‐142‐3p seems to be unique among potential biomarker candidates in MS, since it is an inflammatory miRNA playing a dual role in the immune and central nervous systems. Here, we aimed to verify the impact of miR‐142‐3p circulating in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 58 publications
2
25
1
1
Order By: Relevance
“…Thus, different patterns of miRNA, as well as changes in miRNA expression related to its immunomodulatory effects, could modify the therapeutic response to this drug. There are several articles describing the miRNA changes associated with other disease modifying treatments such as IFN ( 36 40 ), natalizumab ( 41 44 ), dimethyl fumarate ( 45 , 46 ) or fingolimod ( 47 51 ), but less information is available regarding GA ( 52 , 53 ). In one article that analyzed the miRNAs changes in a mouse-EAE model treated with GA, the authors found miR-155.5p, miR-27a.3p, miR-9.5p and miR-350.5p as putative GA-treatment response biomarkers ( 52 ), all of which were associated with an altered polarization of T cells toward a Th1 and Th17 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different patterns of miRNA, as well as changes in miRNA expression related to its immunomodulatory effects, could modify the therapeutic response to this drug. There are several articles describing the miRNA changes associated with other disease modifying treatments such as IFN ( 36 40 ), natalizumab ( 41 44 ), dimethyl fumarate ( 45 , 46 ) or fingolimod ( 47 51 ), but less information is available regarding GA ( 52 , 53 ). In one article that analyzed the miRNAs changes in a mouse-EAE model treated with GA, the authors found miR-155.5p, miR-27a.3p, miR-9.5p and miR-350.5p as putative GA-treatment response biomarkers ( 52 ), all of which were associated with an altered polarization of T cells toward a Th1 and Th17 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in hematopoesis, inflammation, lung development, and response to viral infections (Shrestha et al, 2017). Changes in hsa-miR-142 expression were reported in ALS (Matamala et al, 2018), PD (Liu et al, 2019;Barbagallo et al, 2020), AD (Kumar et al, 2013;Sørensen et al, 2016;Song and Kim, 2017), and especially in MS (Ma et al, 2014;Regev et al, 2016Regev et al, , 2017Regev et al, , 2018Mandolesi et al, 2017;Raheja et al, 2018;De Vito et al, 2022). It was also associated with disease progression in MS and ALS (Regev et al, 2016;Mandolesi et al, 2017;Regev et al, 2017;Matamala et al, 2018;Raheja et al, 2018;Regev et al, 2018;De Vito et al, 2022).…”
Section: Other Mirnasmentioning
confidence: 99%
“…Lower baseline serum contactin-1 concentrations have been associated with long-term disability progression during et al, 2022), and patients with relapsing-remitting MS have significantly lower levels of semaphorin 3a compared with controls (Rezaeepoor et al, 2017). The poxviral IL-1R-like protein and inhibitor of IL-1β converting enzyme may, on the other hand, reduce the IL1β-mediated synaptic dysfunction, possibly leading to exitotoxic damage in both EAE and MS as well as neuroinflammation overall (De Vito et al, 2022;Mandolesi et al, 2017). In IL-1Ra −/− mice with active EAE, IFN-γ, IL-17, and TNF-α production and proliferation were enhanced in IL-1Ra −/− T cells (Matsuki et al, 2006).…”
Section: Neuropathogenic Mechanisms Of Poxvirusesmentioning
confidence: 99%